Pseudo - y - closed - Injective Modules - Arabi, Ahmed Ali; Nayef, Mahdi Saleh (Iraqi Journal of Science, 2024)
In this paper, we introduce new concepts of pseudo- -closed -injective module, and quasi- pseudo- -closed- injective module. This work which is generalization of pseudo-injective modules and y-closed-injective modules. We have provided some characteristics and descriptions of those concepts. CLS-modules have been characterized in terms of pseudo- - closed-injective modules. We have shown the relationships of quasi-pseudo- -closed-injective with other concepts, including a Co-Hopfian, directly finite modules.